Guiding curriculum development of a national research training program in thrombosis medicine: A needs assessment involving faculty and trainees. Issue 162 (February 2018) - Skeith, Leslie; Carrier, Marc; Shivakumar, Sudeep; Langlois, Nicole; Le Gal, Gregoire; Harris, Ilene; Gonsalves, Carol
Abstract: Background: Several barriers exist for training and retention of clinician scientists, including difficulty in navigating research-related tasks in the workplace and insufficient mentorship. Objective: Our aim was to identify what core research knowledge and skills are important for the success of clinician scientists in thrombosis research, and trainees' perceived confidence in those skills, in order to develop a targeted educational intervention. Methods: A pre-tested online survey was administered to trainees and research faculty of the Canadian thrombosis research network, CanVECTOR, between September 2016 and June 2017. The importance (research faculty) and confidence (trainees) of 45 research knowledge/skills were measured using a 5-point Likert scale. Results: The survey response rate was 49% (28/57) for research faculty and 100% (10/10) for trainees. All research faculty rated developing a good research question, grant writing and writing strategies for successful publication as 'very' or 'extremely' important for trainees to learn to better transition in becoming independent researchers. Other important areas included practical aspects of research. A qualitative thematic analysis of open text responses identified 'time management' and 'leadership and teamwork' as additional important research skills. Confidence reported for each topic varied across trainees. There were three research knowledge and/or skills that ≥ 75% of research faculty deemed highly important and ≥ 50% of trainees reported lacking confidence in: grant writing, the peer-review grant process, and knowledge translation strategies. Conclusions: Developing a good research question, communicating research ideas and results and the practical aspects of research are important areas to focus future efforts in thrombosis research training.